Synthesis and characterization of metal phthalocyanine bearing carboxylic acid anchoring groups for nanoparticle dispersion and their application to color filters. (January 2021) - Namgoong, Jin Woong; Kim, Hong Mo; Kim, Se Hun; Yuk, Sim Bum; Choi, Jun; Kim, Jae Pil
Abstract: The color filter is an integral part of the white-OLED display, LCD, and CMOS image sensor. This study aimed to improve the color property and thermal stability of a dye-based color filter. For this purpose, the dispersed-dye-based color filter was developed using dye dispersions. Six metal (Cu, Zn) phthalocyanine dyes bearing bulky benzoic acid groups and chlorine were synthesized and their optimized molecular structures, electrostatic potential surfaces, optical properties, thermal stability, and dispersion properties were determined using computational modeling, UV–Vis spectrometry, TGA, and DLS. The synthesized dyes showed suitable spectral properties and thermal stability for green color filters. Among the dyes, polychloro zinc phthalocyanine had superior dispersion properties owing to its distorted geometric structure. A dispersant containing both amine and ammonium groups as anchors was effective in dispersing the dyes. The color filters with the dye dispersions were prepared by spin-coating. As the bulkiness of the dye increased, their dispersibility was enhanced but their thermal stability decreased. On the other hand, it was observed that the higher the dispersibility of the dye, the superior the color properties and the smaller the thickness of the films. All color filters showed better stability than the traditional soluble-dye-based color filter. This study confirmed that the dispersed-dye-based color filter with fine dye particles exhibits superior stability compared with the dye-based color filter, without compromising color properties. Graphical abstract: Image 1 Highlights: 3c-ZnPc which have acid anchors and chlorines showed superior dispersion properties and spectral characteristics. The saddle structure and the acid anchors of Pc dyes help in the formation and stabilization of its nanoparticles. Polychloro ZnPc derivative bearing carboxylic acid is favorable for the well-dispersed fine particles for the colorfilter.